Therapeutic Potential of Bioactive Compounds in Honey for Treating Osteoarthritis - Martinez-Armenta, Carlos; Camacho-Rea, María Carmen; Martínez-Nava, Gabriela Angélica; Espinosa-Velázquez, Rocio; Pineda, Carlos; Gomez-Quiroz, Luis Enrique; López-Reyes, Alberto (Frontiers in Pharmacology, 2021)
Dysregulation of joint tissue homeostasis induces articular degenerative changes and musculoskeletal diseases such as osteoarthritis. This pathology represents the first cause of motor disability in individuals over 60 years of age, impacting their quality of life and the costs of health systems. Nowadays, pharmacological treatments for cartilage disease have failed to achieve full tissue regeneration, resulting in a functional loss of the joint; therefore, joint arthroplasty is the gold standard procedure to cure this pathology in severe cases of OA. A different treatment is the use of anti-inflammatory drugs which mitigate pain and inflammation in some degree, but without significant inhibition of disease progression. In this sense, new therapeutic alternatives based on natural compounds have been proposed to delay osteoarthritis progression, particularly those agents that regulate articular homeostasis. Preclinical studies have shown a therapeutic application of honey and its bioactive compounds, ranging from treating wounds, coughs, skin infections, and are also used as a biological stimulant by exerting antioxidant and anti-inflammatory properties. In this article, we reviewed the current medicinal applications of honey with particular emphasis on its use regulating articular homeostasis by inhibiting inflammation and oxidative stress.